Wie können Schlüsselwörter in den erbaulichen Textsorten am Beispiel der protestantischen Leichenpredigten bestimmt werden - Ireneusz Gaworski (Beiträge zur Allgemeinen und Vergleichenden Sprachwissenschaft)
The term keyword, created in 1954 by Pierre Guiraud, is also used in contemporary linguistics to describe words that, because of their frequency of occurrence, are characteristic of a particular text, the genre of a text or the writer's style. The indication of keywords defined in this way in Protestant funeral sermons, which are one of the most representative genres of German moralizing literature of the 16th and 17th centuries, is difficult and often does not provide an answer to the question of what is referred to in a given text. Based on the analysis of a sermon written by Johannes Bugenhagen on the death of Martin Luther (1546), the paper attempts to develop criteria for the selection of keywords in this genre of texts.